1999
DOI: 10.1073/pnas.96.26.14911
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of the Ras-related protein associated with diabetes Rad and the putative tumor metastasis suppressor NM23 provides a novel mechanism of GTPase regulation

Abstract: Rad is the prototypic member of a new class of Ras-related GTPases. Purification of the GTPase-activating protein (GAP) for Rad revealed nm23, a putative tumor metastasis suppressor and a development gene in Drosophila. Antibodies against nm23 depleted Rad-GAP activity from human skeletal muscle cytosol, and bacterially expressed nm23 reconstituted the activity. The GAP activity of nm23 was specific for Rad, was absent with the S105N putative dominant negative mutant of Rad, and was reduced with mutations of n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
91
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(95 citation statements)
references
References 45 publications
4
91
0
Order By: Relevance
“…NM23, which was identified as GTPase-activating protein and guanine nucleotide exchange factor (GEF) for Rad, acts as Gem-GEF in vitro (42). It has been shown that NM23 inhibits Rad-induced growth and tumorigenicity of breast cancer in breast tissues (43).…”
Section: Discussionmentioning
confidence: 99%
“…NM23, which was identified as GTPase-activating protein and guanine nucleotide exchange factor (GEF) for Rad, acts as Gem-GEF in vitro (42). It has been shown that NM23 inhibits Rad-induced growth and tumorigenicity of breast cancer in breast tissues (43).…”
Section: Discussionmentioning
confidence: 99%
“…While these proteins have not yet been identified, the in vitro GTP/GDP state of Rad has been found to be modified by the tumor suppressor nm23, which can either phosphorylate GDP or dephosphoryate GTP while the nucleotide is bound to Rad [14]. It remains to be determined whether nm23 functions as an in vivo regulator of Rad, or regulates the actions of other RGK proteins.…”
Section: Rgk Proteins Are Guanine Nucleotide-binding Proteinsmentioning
confidence: 99%
“…NDPK is capable of maintaining nucleotide levels in mammals, implying NDPK may be a critical component of G protein-mediated signaling (2)(3)(4)(5)(6). Mammalian NDPK is a multifunctional enzyme, involved in the regulation of growth and development (7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%